The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.31235/osf.io/6wjxc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socioeconomic Roots of Academic Faculty

Abstract: Tenure-track faculty play a special role in society: they train future researchers, and they produce much of the scholarship that drives scientific, technological, and social innovation. However, the professoriate has never been demographically representative of the general population it serves. For example in the United States, Black and Hispanic scholars are underrepresented across the tenure-track, and while women’s representation has increased over time, they remain a minority in many academic fields. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Individuals who are the first in their family or social network to enter a PhD program may experience a profound "network gap" in that they are less aware of ways in which professional positions are identified and pursued. 24 In ideal circumstances, faculty mentors can play a key role in helping doctoral students identify and navigate these unwritten norms and expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who are the first in their family or social network to enter a PhD program may experience a profound "network gap" in that they are less aware of ways in which professional positions are identified and pursued. 24 In ideal circumstances, faculty mentors can play a key role in helping doctoral students identify and navigate these unwritten norms and expectations.…”
Section: Discussionmentioning
confidence: 99%
“…Faculty hiring plays a fundamental role in shaping the composition of the scientific workforce [5,23], and hence in determining the demographic composition of scientists [23], and what and whose particular scientific questions are studied [24]. Although past work has shown that doctoral prestige is predictive of whose graduates are hired as faculty [5,6,29], we have lacked a deeper understanding the dynamics of and mechanisms that create and maintain prestige hierarchies [3,13,17,22,28].…”
Section: Discussionmentioning
confidence: 99%
“…Few data are available regarding rural individuals in science and research. For instance, only three studies have been conducted in North America examining how class and socioeconomic origin affect obtaining professorship, and none focused on rurality [1][2][3]. The National Science Foundation, which conducts the Survey of Earned Doctorates (SED), could provide valuable insights by reporting geographical workforce data.…”
Section: Drivers Of Rural Educational Inequitymentioning
confidence: 99%
“…Parental educational attainment is another established predictor of postsecondary outcomes and is substantially lower in rural communities [5]. Parental education influences whether children are encouraged to attend college and parental ability to assist children with success in academia [1,9]. First-generation students (no bachelor's degree held by either parent) are 15% less likely to complete a bachelor's degree within 6 years [10].…”
Section: Drivers Of Rural Educational Inequitymentioning
confidence: 99%
See 1 more Smart Citation